A Case of Pernio Associated with Cold Agglutinin Positivity in an Unusual Location - Gönül, Müzeyyen; Özge Keseroğlu, Havva; Işıl Kurmuş, Gökçe; Han, Ünsal; Ergin, Can (Journal of Dermatologic Research And Therapy, 2016)
Pernio is an inflammatory disease that is usually characterized by the development of cold-induced erythrocyanotic skin lesions located in acral regions. Diagnosis is difficult if lesions are present in rare locations. A 21-year-old female suffering from fatigue presented with a 4-day history of painful, purple lesions on both thighs. She worked as a cashier, wore tight clothing, and was otherwise healthy except for mild obesity. Dermatological examination revealed tender and painful edematous papules and plaques on the outer aspects of her thighs. The patient was diagnosed with pernio based on her medical history, and clinical and histological findings. Laboratory tests were normal except for her cold agglutinin titer (1:4). Pernio rarely occurs on the thigh, except in people who ride horses. However, it sometimes occurs in non-riders depending on lifestyle and environmental conditions. Therefore, lesions in this region must be confirmed by a thorough medical history and evaluation of clinical and histopathological findings. Cold agglutinins may be associated with this disease.
Keywords: Pernio; Cold Agglutinin; Skin Lesions; Acral Regions; Inflammatory Disease